Indonesia's Creative Industry towards the ASEAN Economic Community - Atika Marzaman (Journal of World Trade Studies, 2013)
Recent development has witnessed a significant contribution of creative economies to economic growth worldwide. This article intends to map the position of Indonesia's creative industry, not only in the Association of South East Asian Nations (ASEAN) market, but also in the wider global trading system. Findings show that in some ASEAN countries, the creative industries sector has been able to play an important role in economic development and contribute greatly to GDR This has posed a great challenge for Indonesia's creative industry to compete in an increasingly competitive regional market. Further finding demonstrate that the Indonesian government has been implementing policies to endorse creative economy. These include supporting the Small and Medium Enterprises (SMEs) as significant actors in this industry and also implementing policies to increase product value through innovation, as well as endorsing the establishment of creative communities at the regional level. In addition, enhancing the relations among government, private sector, and academia is seen as crucial in strengthening Indonesia's creative industry sector.